2013
DOI: 10.1007/s13277-013-1396-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hepatoma cells function of luteolin through inducing apoptosis and cell cycle arrest

Abstract: The aim of this study is to explore the apoptotic induction and cell cycle arrest function of luteolin on the liver cancer cells and the related mechanism. The liver cancer cell line SMMC-7721, BEL-7402, and normal liver cells HL-7702 were treated with different concentrations of luteolin. Cell proliferation ability was tested. Morphological changes of the apoptotic cells were observed under inverted fluorescence microscope after Hoechst33342 staining. We investigated the effect of luteolin on cell cycling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Furthermore, it has been documented that luteolin could arrest the cell cycle and induce apoptosis in a wide variety of cancer cells in vitro , including prostate cancer cells (20), AGS human gastric cancer cells (21,22), SMMC7721 liver cancer cells (23), COLO205 human colorectal cancer cells and HeLa human cervical cancer cells (24). It has also been reported that luteolin was able to significantly decrease colon cancer incidence and the number of tumors per rat when administered at the initiation and post-initiation stages of carcinogenesis (25).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been documented that luteolin could arrest the cell cycle and induce apoptosis in a wide variety of cancer cells in vitro , including prostate cancer cells (20), AGS human gastric cancer cells (21,22), SMMC7721 liver cancer cells (23), COLO205 human colorectal cancer cells and HeLa human cervical cancer cells (24). It has also been reported that luteolin was able to significantly decrease colon cancer incidence and the number of tumors per rat when administered at the initiation and post-initiation stages of carcinogenesis (25).…”
Section: Introductionmentioning
confidence: 99%
“…[59,60] Detection methods of caspasee xpression primarily rely on RT-PCR, flow cytometric based analysis, colori-/fluorometric assays,a nd SPR technology. [61][62][63][64] Recently,t ime-resolved FRET technology has been developed to detect caspase-3. [65] Althoughmost of thesemethods are promisingi nthe laboratory, unfortunately,they are usually time consuming, labor intensive, or require highly technical experience and complex instrumentation.…”
Section: Enzyme Activation During Apoptosismentioning
confidence: 99%
“…If apoptosis induced by MST-312 pretreatment and X-ray irradiation is through the mitochondrial pathway, the mitochondrial membrane integrity will be damaged at the early stage of cell apoptosis [7]. The JC-1 fluorescence changes from red to green following the decline of mitochondrial membrane potential.…”
Section: Mst-312 Pretreatment Followed By X-ray Irradiation Elevated mentioning
confidence: 99%